Effect analysis of microwave heating on selective laser sintered CNT/PA12 nanocomposites - Hadi Mulyadi Suyoto (2018)
Additive manufacturing (AM), also known as 3D printing, have gained popularity in recent years especially in the engineering industries. Selective laser sintering (SLS) is one of the manufacturing process and has been a popular choice for engineers due to its low cost per part, high productivity and ideal range of applications. SLS is a process where powders which can be in a form of plastic, ceramic or glass, are fused together to form three-dimensional object. The fusion is made possible by the heat generated from a high power laser. SLS allows operators and designer a greater flexibility when manufacturing parts compared to conventional processes. However, some of the main obstacles in this technology are the limited range of materials, failure to completely meet mechanical requirements and the mechanical failure that can occur due to the unsteady weld between filament traces. Polyamide 12 is one of the most common polymer material used in SLS. However, there is a need to further investigate the composition of powder used so that sintered parts can meet the mechanical requirements. Carbon nanotubes (CNTs) are tube shaped material made of carbon with diameters measurable by nanometer scale. In this study, CNTs is used as a filler to PA12 due to its high strength and low weight ratio. As a result, well dispersed PA12-CNT nanocomposite powders is used as the main material. However, potential CNTs poses a few problems due to its limited heating time above critical sintering temperature. Filament bonding can only occur if polymer is heated above its critical sintering temperature. Failure to do so results if incomplete filament bonding which leads to mechanical failure. In previous studies, heated air nozzles were used to increase the heating time. However, this causes disruption to its morphology which leads to warping of structure. In this study, heat is directly applied to the polymer by the means of microwave. The wave length of a microwave is much smaller than filament trace dimensions. When exposed to microwave radiation, CNTs are knows to rapidly evolve. This effect can take place in both single wall CNTs and multiwall CNTs.